2021
DOI: 10.1177/21582440211058198
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating Creativity of Graphic Design and Multimedia Students: The Perceptions of Arab Faculty and Experts

Abstract: While a consensus has emerged on the importance of creativity in graphic design and multimedia field, little systematic research has attempted to understand its facilitators or inhibitors in the graphic and multimedia education across colleges and universities. The current investigation surveys a sample of experts as well as professors teaching across the Arab World concerning their perceptions on the most significant correlates of creative thinking among students. Results point to the importance of: (1) instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
0
0
1
Order By: Relevance
“…Since the fail-safe N is 10358 and higher than the value of 5k + 10, it can be concluded that there is no publication bias in this metaanalysis study. Research on creativity in education has shown a strong relationship between the learning strategies used in the classroom and students' levels of creative thinking (Elkilany & Yousef, 2021). Support to continue to improve student creativity must continue to be carried out either through related institutions or in the field of research.…”
Section: Resultsmentioning
confidence: 99%
“…Since the fail-safe N is 10358 and higher than the value of 5k + 10, it can be concluded that there is no publication bias in this metaanalysis study. Research on creativity in education has shown a strong relationship between the learning strategies used in the classroom and students' levels of creative thinking (Elkilany & Yousef, 2021). Support to continue to improve student creativity must continue to be carried out either through related institutions or in the field of research.…”
Section: Resultsmentioning
confidence: 99%
“…El impulso del pensamiento creativo se ha basado, en cierta forma, en la colaboración entre pares, la retroalimentación continua, y la evolución de los proyectos, pues la reflexión en el contexto del diseño es un componente clave para mejorar las ideas. Esta habilidad, por lo tanto, también representa una forma de comunicar las propuestas y adecuarlas a un entorno, donde la interdisciplina representa un aporte a la formación del profesional (Elkilany & Yousef, 2021). Sin embargo, se han presentado ciertos retos para la interdisciplina en el diseño.…”
Section: Diversas Concepciones Del Pensamiento Creativo Al Contemplar...unclassified